Care management from the nursing professional's perception in times of Sars-CoV-2 (Covid-19) pandemic in a Peruvian Public Hospital: Implications for patient safety (GnosisWisdom, 2023)
Objective. To determine the relationship between care management and patient safety from the nursing professional's perception in times of Sars-CoV-2 (Covid-19) pandemic at the Departmental Hospital of Huancavelica.Materials and Methods. Type of study was descriptive, descriptive level, non-experimental design, descriptive transactional, scientific method and documentary analysis. The population and sample consisted of nursing professionals, and the survey technique was used.Results. 46.9% of nursing professionals of the Departmental Hospital of Huancavelica perceive a good nursing care management and therefore an acceptable condition in the framework of patient safety, 24.0%; manifest an excellent nursing care management and acceptable in reference to patient safety.Conclusions. The nursing professionals considered to be some of the first line expresses its great responsibility to ensure the recovery of the person through the management of care and patient safety in the units providing health services at the hospital level.
Keywords: Care management; patient safety; nursing; hospital